Perubahan Penggunaan Tanah Pertanian Ke Non Pertanian Di Kantor Pertanahan Karanganyar - Hapsari, Devy Silvia; , Darsono, S.H., M.Hum (2016)
Change of use of land for agriculture to non-agricultural use for getting increased. Especially for the Indonesian people, this phenomenon can bring serious problems later if not immediately anticipated from now. This study aims to investigate the implementation of changes in the use of agricultural land to non-agricultural land office Karanganyar district and barriers that occur at the time of application for change of use of agricultural land to non-agricultural land office Karanganyar. This research method using descriptive empirical approach.Using this type of primary data and secondary data. Data collection techniques used through the study of literature, documentation, a list of questions and the interview list. By using qualitative data analysis. Results obtained from this research that the implementation of the change of use of agricultural land to non agricultural from the applicant and know the resistance barriers that exist in it, understand and develop a theory that was obtained, so that it can be applied in practice courts invitation expectation that will be of help in thinking to solve the problems faced in the transfer function of agricultural land to non-agricultural. Keywords: Changes in Land Use, Land Transfer Function Process Into Non-Agricultural Farms